Pengaruh Self Assessment System, Pengetahuan dan Pemahaman Perpajakan serta Machiavellian terhadap Kepatuhan Wajib Pajak Orang Pribadi - I Komang Sukra Dinata; I Made Marsa Arsana; Anak Agung Gde Mantra Suarjana (Jurnal Bisnis dan Kewirausahaan, 2023)
The problem in this research is: Does the self-assessment system have an impact on WP OP compliance? Does knowledge and understanding of taxation have an impact on WP OP compliance? Does Machiavellian impact WP OP compliance? Does the self-assessment system, knowledge and understanding of taxation, and Machiavellian simultaneously have an impact on WP OP compliance? Research objective: To analyze the impact of the self-assessment system on WP OP compliance. Analyze the impact of knowledge and understanding of taxation on WP OP compliance. Analyze the impact of Machiavellian on WP OP compliance. Analyzing the impact of the self-assessment system, knowledge and understanding of taxation, and Machiavellian simultaneously on WP OP compliance. Data collection was carried out using a questionnaire technique. The number of samples is 99 people WP OP. The data processing technique uses multiple linear regression. The results of data analysis with a significance of 0.05 indicate that the self-assessment system has a positive and significant impact on WP OP compliance. Knowledge and understanding of taxation has a positive and significant impact on taxpayer OP compliance. Machiavellian has a negative and insignificant impact on WP OP compliance. Self-assessment system, knowledge and understanding of taxation, and Machiavellian simultaneously impact W P OP compliance. The advice given is that the implementation of the Self-assessment system continues to be improved and the socialization of tax rules continues to be encouraged in an effort to increase knowledge and understanding of taxation for taxpayers.